Cross‐talk between EGF and BMP9 signalling pathways regulates the osteogenic differentiation of mesenchymal stem cells. Issue 9 (11th July 2013) - Liu, Xing; Qin, Jiaqiang; Luo, Qing; Bi, Yang; Zhu, Gaohui; Jiang, Wei; Kim, Stephanie H.; Li, Mi; Su, Yuxi; Nan, Guoxin; Cui, Jing; Zhang, Wenwen; et al.
Abstract: Mesenchymal stem cells (MSCs) are multipotent progenitors, which give rise to several lineages, including bone, cartilage and fat. Epidermal growth factor (EGF) stimulates cell growth, proliferation and differentiation. EGF acts by binding with high affinity to epidermal growth factor receptor (EGFR) on the cell surface and stimulating the intrinsic protein tyrosine kinase activity of its receptor, which initiates a signal transduction cascade causing a variety of biochemical changes within the cell and regulating cell proliferation and differentiation. We have identified BMP9 as one of the most osteogenic BMPs in MSCs. In this study, we investigate if EGF signalling cross‐talks with BMP9 and regulates BMP9‐induced osteogenic differentiation. We find that EGF potentiates BMP9‐induced early and late osteogenic markers of MSCs in vitro, which can be effectively blunted by EGFR inhibitors Gefitinib and Erlotinib or receptor tyrosine kinase inhibitors AG‐1478 and AG‐494 in a dose‐ and time‐dependent manner. Furthermore, EGF significantly augments BMP9‐induced bone formation in the cultured mouse foetal limb explants. In vivo stem cell implantation experiment reveals that exogenous expression of EGF in MSCs can effectively potentiate BMP9‐induced ectopic bone formation, yielding larger and more mature bone masses. Interestingly, we find that, while EGF can induce BMP9 expression in MSCs, EGFR expression is directly up‐regulated by BMP9 through Smad1/5/8 signalling pathway. Thus, the cross‐talk between EGF and BMP9 signalling pathways in MSCs may underline their important roles in regulating osteogenic differentiation. Harnessing the synergy between BMP9 and EGF should be beneficial for enhancing osteogenesis in regenerative medicine.